Biomonitoring as an Effort to Monitor River Water Quality with Parameters of BOD, DO, pH, TDS and the Presence of Macrozoobenthos in the Rolak River Area, Surabaya City - Ummuzzahra, Fitria; Kholish, Nadia Rana Abiyya; Adji, Adhiatma; Nofitri, Audi Ananda; Pertiwi, Diandra Dieva; Nurdiansyah, Alfian; Baharudin, Faizal Abdillah; Jalalludin, Ahmad Jalali; Putra, Rico Thomas (Faculty of Civil Engeneering and Planning - ITATS, 2023)
Many of the person who built settlements in riverbank areas, this allows residents in riverbank areasto become accustomed to disposing of waste directly into the river. In the end, this waste threatens the success of river flow, polluted river water has a serious impact on the health and quality of the environment around the riverbanks, such as the negative impact caused by this pollution, for example, such as health which has an impact on the surrounding environment or others. Because it is important to understand the natural health relationship, this study chose a river area that is located around the Rolak area of Surabaya, this place was chosen because the area is around a densely populated area and an industrial area. So that it can be used as research because the area certainly has a high level of pollution. As a result of the impact of the many residential and industrial areas around the river, the biomonitoring method is carried out to identify river pollution from its physical habitat by monitoring environmental health using living organisms in the river. Therefore the biomonitoring method can be applied because the advantages of this method can also be used including helping identify by using test parameters such as measuring pH, temperature and oxygen content in river water. that has been done before. Then the biotic examination can be used as a guide that can represent the quality of a body of water, from observations at several points the river is known to have a color that tends to be brownish due to turbidity levels, the pH parameters at each sample point are classified as normal and for Total Dissolved Solid (TDS) there is content of 339 mg/l, this is thought to be due to the source of domestic waste pollution from residents' settlements around the river banks. For DO test results there are only five points that meet quality standards. As for the diversity of bioindicators at each point, such as the presence of weeds at the first point, while the presence of water hyacinth can only be seen at the third and fourth points, the macrozoobenthos that are commonly found in the mangrove area are from the Mollusca, Annelida, and Arthropoda.